Criminal Law Policy in Handling Criminal Acts of Drug Abuse Among Adolescents (Case Study at Cirebon City Police) - Subagja, Riki; Winjaya Laksana, Andri (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Drug and illicit drug abuse is an international crime and an extra ordinary crime. The definition is a crime that has a very large and multidimensional impact on social, cultural, economic and political and the negative impact caused by this crime is so terrible. The purpose of this study is to determine and analyze criminal law policies in overcoming the crime of drug abuse among teenagers. To determine and analyze the obstacles faced by the police in overcoming the crime of drug abuse among teenagers and their solutions. The method used by the researcher is a sociological legal aproach and the specifications in this study are descriptive. The sources and types of data in this study are primary data obtained through interviews and secondary data obtained from literature studies. The data is analyzed qualitatively using the theory of the rule of law and the theory of the legal system. Based on the results of the study, the Criminal Law Policy in overcoming the crime of drug abuse among adolescents focuses on law enforcement, rehabilitation, and prevention. The Narcotics Law (Narcotics Law) is the main legal basis, with criminal sanctions that vary depending on the type and amount of narcotics involved. Overcoming drug crimes, including synthetic tobacco and crystal methamphetamine, among adolescents requires a comprehensive aproach. In addition to strict law enforcement, effective rehabilitation and prevention are needed to prevent drug abuse among adolescents. The main obstacles in overcoming drug crimes, especially among adolescents, include: easy access to drugs, lack of understanding of the dangers of drugs, and lack of adequate suport and rehabilitation. Solutions that can be taken include intensive education, strict law enforcement, and social suport and rehabilitation for drug addicts.